Intercruzando saberes na Educação de Jovens e Adultos (EJA) - Rosa, Ana Iara Dalla (2020)
ABSTRACT: This study has as its theme literacy in Youth and Adult Education (EJA) and is linked to the Research Group Literacy and School Literacy (ALFALE), of the Graduate Program of the Institute of Human and Social Sciences of the Federal University from Mato Grosso, the research line “Languages, culture and construction of knowledge: historical and contemporary perspectives". Therefore, it comes from the constant inquiries about the challenges in the learning processes, mainly regarding literacy in EJA, a modality that has its own characteristics and challenges, involving both illiterate students and those with low education level. In this sense, the following question is pertinent: does the subject's life history interfere in the appropriation of reading and writing? And: Being able to read and writing autonomously, changes and gives new meaning to the person? It can seem very subjective to answer these questions, especially in the case of research that aims to discuss themes related to language, but the human being is constituted by language and, therefore, these questions are added to this perspective. Thus, the present research, carried out with a class of EJA belonging to the Municipal Education Network of Rondonópolis / MT, has the general objective to identify the processes of appropriation of reading and writing by EJA students, considering life narratives as elements that give a new meaning to this appropriation and intend, with the specific objectives, to understand which are the elements that impacted a late literacy; identify possible relationships between the facts of life and the construction of linguistic knowledge; and, finally, punctuate elements in the language learning process that contribute to the permanence of these students in the EJA. It is important to reflect on the literacy of these adults from a sociocultural perspective, without neglecting personal aspects, as they can interfere in the process of appropriation of the Alphabetical Writing System (SEA), being decisive in the permanence or dropping out of school. Thus, to support this discussion, we rely on Freire (2016; 2018a; 2018b) and Arroyo (1991; 2011; 2017) to discuss EJA and Soares (2017a; 2017b; 2018) to talk about literacy. Inserted in the qualitative approach, it is a participatory research. For data collection, a semi-structured interview with 4 students was used, which were recorded with a smartphone, individual notebooks containing the activities of the first and second semesters of 2019 and the researcher's notebook. For data analysis, we considered the variables age and life histories reported by the participants during the interviews. The results of this research, based on the items previously described and added to the observations, theoretical studies, activities developed by the students, listening to the reports of this group's life and the interpretation of the facts, by the researcher, constituted this dissertation which, in addition to providing an attentive look at EJA, makes it possible to expand the reflections and political and pedagogical dialogues for this educational segment still so neglected by public educational policies.